ANTI-INFLAMMATORY ACTIVITY OF SIDDHA POLYHERBAL FORMULATION SEVVIYADHI CHOORANAM ON CARRAGEENAN INDUCED PAW EDEMA IN WISTAR ALBINO RATS - S., SHAMSHALNIHA; N., ANBU (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: The aim of the study was to explore the anti-inflammatory activity of Siddha polyherbal formulation Sevviyadhi chooranam in Carrageenan induced paw edema in wistar albino rats, and compared with the standard drug Indomethacin. Methods: The Siddha polyherbal formulation Sevviyadhi chooranam indicated for sinusitis was prepared based on GMP (Good Clinical Practice) guidelines. Study procedure was approved by Institutional Animal Ethics Committee (IAEC). The experimental animals were measured for paw edema volume at 1, 2, 3, 4, 5 h using Plethysmometer (Model 7150 UGO Basile, Italy). Edema was expressed as mean increase in paw volume relative to control animals. And then, findings were compared with Indomethacin (Standard drug). Results: The findings revealed that test drug Sevviyadhi chooranam at higher dosage 200 mg/kg (Group V) had equal effect on anti-inflammatory activity with percentage protection of 93.2% when compared with the standard drug Indomethacin at about 40 mg/kg (Group III) with percentage protection 93.2%. However, the test drug Sevviyadhi chooranam at a higher dosage 200 mg/kg (Group V) with a percentage protection 93.2% was highly effective when compared with lower dosage about 100 mg/kg (Group IV) with a percentage protection 27.12%. Hence, the study resulted that the Siddha polyherbal formulation Sevviyadhi chooranam has an optimistic anti-inflammatory activity with more therapeutic value. Conclusion: The study concluded that the Siddha polyherbal formulation Sevviyadhi chooranam has a promising anti-inflammatory activity, probably due to the presence of biologically active phytocompounds. However, it is important to admit that there are some scientific evidences of the potential actions of these phytocompounds in anti-inflammatory activity.